Architectural Exploration of an FPGA-based Hardware Accelerator for the Gaussian Filter using Approximate Computing - Sborz, Guilherme; Viel, Felipe; Zeferino, Cesar (Anais Estendidos do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2020)
The growing use of computer vision applications has increased the demand for efficient image processing implementations. These applications have constraints that, in some cases, can only be met by dedicated hardware implementations. This work presents architectures that apply approximate computing techniques to improve efficiency and scalability for implementing digital image filters on FPGA. These architectures were implemented as hardware accelerators for an embedded processor in an FPGA-based System-on-Chip. The results show that the use of approximate computing techniques can reduce costs without affecting results for the target application, which is an essential feature for further acceleration using parallel processing on hardware.